Jihadism in Africa: Local causes, regional expansion, international alliances - Guido Steinberg; Annette Weber (Stiftung Wissenschaft und Politik (SWP), 2015)
The transnational terrorism of the twenty-first century feeds on local and regional conflicts, without which most terrorist groups would never have appeared in the first place. That is the case in Afghanistan and Pakistan, Syria and Iraq, as well as in North and West Africa and the Horn of Africa. Groups like al-Shabaab, Boko Haram and al-Qaeda in Somalia, Nigeria and Algeria operate within and profit from local conflicts. Anyone wishing to understand (and counteract) such forces must delve into the specific circumstances within these countries, as well as others such as Mali and the Sahel region. The effects of the multitude of personal ties, recruiting networks and ideological influences connecting jihadist movements are felt across countries, regions and even continents. Yet understanding the specific conditions on the ground remains key to analysing events currently playing out in the so-called African arc of instability that runs from East Africa to Mauritania and extends as far north as Tunisia and south to northern Nigeria. (SWP Research Paper)
Keywords: 320